The Role of Local Government in Accelerating Sustainable Economic Development in Sungai Penuh City - Silvia Rahayu; Erni Febrina Harahap; Dorris Yadewani (The Future of Education Journal, 2026)
This study aims to analyze the role of local government in promoting sustainable economic development in Sungai Penuh City. The research employs a descriptive qualitative method with a literature study approach. The findings reveal that the local government plays a central role as: (1) a catalyst for the transition toward a green economy, (2) an integrator of diverse local interests and potentials, (3) a guardian of environmental sustainability and local wisdom, and (4) an innovator in formulating contextually appropriate solutions. By leveraging its strategic location within a conservation area and the local wisdom of its communities, Sungai Penuh has the potential to become a model for ecosystem-based sustainable urban development that preserves the Kerinci Seblat National Park (TNKS) while fostering inclusive prosperity for its citizens.